N-Acetylcysteine protects inner ear hair cells and spiral ganglion neurons from manganese exposure by regulating ROS levels. (5th September 2017) - Wang, Weilong; Li, Dan; Ding, Xuerui; Zhao, Qianqian; Chen, Jiawei; Tian, Keyong; Qiu, Yang; Lu, Lianjun
Highlights: Mn induced inner ear hair cells and spiral ganglion neurons (SGN) apoptosis. The Mn-induced increase in the ROS level was attenuated by NAC. NAC protected inner ear hair cells, ANF and SGN from Mn exposure. Abstract: Manganese (Mn) is an indispensable cofactor for many enzymes and a basic factor for many reproductive and metabolic pathways. However, exposure to high concentrations of Mn can result in deleterious effects on the central nervous system and peripheral nerves, including nerves associated with the auditory system. Based on our studies of cochlear organotypic cultures, Mn exposure induces a significant loss of hair cells (HCs), auditory nerve fibers (ANFs) and spiral ganglion neurons (SGNs) in a concentration-dependent manner. Additionally, N -acetylcysteine (NAC), a glutathione (GSH) provider and a direct scavenger of reactive oxygen species (ROS), clearly decreases Mn-induced ROS accumulation, caspase-3 activation and TUNEL staining, which indicate increased cell survival. Based on these results, Mn exposure exerts ototoxic and neurotoxic effects on the auditory system. Furthermore, 20 mM NAC may prevent 1 mM Mn-induced hair cell loss and axonal degeneration, indicating that NAC could be a promising drug for clinical applications.